1999
DOI: 10.1073/pnas.96.14.7980
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of the p120 ctn Armadillo-like catenin is counteracted by a nuclear export signal and by E-cadherin expression

Abstract: The Armadillo protein p120 ctn associates with the cytoplasmic domain of cadherins and accumulates at cell-cell junctions. Particular Armadillo proteins such as ␤-catenin and plakophilins show a partly nuclear location, suggesting gene-regulatory activities. For different human E-cadherin-negative carcinoma cancer cell lines we found expression of endogenous p120 ctn in the nucleus. Expression of E-cadherin directed p120 ctn out of the nucleus. Previously, we reported that the human p120 ctn gene might encode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
136
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 51 publications
11
136
0
Order By: Relevance
“…This raises the exciting possibility that Armadillo repeat proteins possess intrinsic nuclear import ability. Consistent with this idea, we and others have detected nuclear p120 ctn , particularly in cells of tumor lineage or in cells lacking functional cadherins (our unpublished data) (RoczniakFerguson and Reynolds, 2003;van Hengel et al, 1999). Interestingly, the nuclear localization of p120 ctn appears to be an isoform-specific phenomenon; all isoforms capable of inducing branching (e.g.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This raises the exciting possibility that Armadillo repeat proteins possess intrinsic nuclear import ability. Consistent with this idea, we and others have detected nuclear p120 ctn , particularly in cells of tumor lineage or in cells lacking functional cadherins (our unpublished data) (RoczniakFerguson and Reynolds, 2003;van Hengel et al, 1999). Interestingly, the nuclear localization of p120 ctn appears to be an isoform-specific phenomenon; all isoforms capable of inducing branching (e.g.…”
supporting
confidence: 85%
“…This suggests that alternative NESs may facilitate the nuclear export of p120 ctn splice variants lacking exon B. Consistent with this idea, some isoforms of p120 ctn lacking exon B are sensitive to leptomycin B (LMB), a specific inhibitor of CRM-1-mediated nuclear export (our unpublished data) (Roczniak-Ferguson and Reynolds, 2003;van Hengel et al, 1999). These results suggest that p120 ctn is capable of nucleocytoplasmic shuttling in a CRM-I-dependent manner.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…32 The Armadillo sequence-rich protein d-catenin, associates with the cytoplasmic domain of E-cadherin and together with b-catenin and acatenin accumulates at cell-cell junctions. An increased level of cytoplasmic d-catenin has been found in breast carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to ␤-catenin, it can be detected in the nucleus (34), where it interacts with the transcriptional factor Kaiso (6). Studies performed with Xenopus laevis have demonstrated that association of p120-catenin relieves the repression caused by Kaiso on Wnt signaling (17,25).…”
mentioning
confidence: 99%